The assessment of endometrial pathology and tubal patency of infertile patients: MR-HSG and X-ray HSG - Turan, Arzu; Aslan, Halil; Colcimen, Nese; Celiker, Fatma Beyazal; Demirtas, Meryem (International Journal of Research in Medical Sciences, 2017)
Background: Infertility is an important disorder for the pairs. Genetic, endocrine disorders or structural genital abnormalities can be cause. The cause of infertility can be determined with careful. Methods: Although it can be reported that ultrasound with saline solution or contrast enhanced hystero salpingo-sonography is the best method to evaluate the uterine cavity and Fallopian tube patency, conventional hysterosalpingography (X-ray-HSG) remains the most commonly used procedure for imaging the uterine cavity and the fallopian tube patency in the evaluation of female infertility. But ionizing radiation to genital organs is the most important problem for X-ray-HSG. Results: For this reason, they are still working on new methods to investigate female infertility as an alternative to X-ray HSGMRI is a favorite method because of excellent image characterization for the female genitals. Conclusions: In this study, the diagnostic performance of MR-HSG was compared with X-ray-HSG which was accepted as a gold standard for detection of tubal patency and pathology of the endometrial cavity.